2022
DOI: 10.3390/toxics10030126
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Storage Conditions and Type of Clearomizers on the Increase of Heavy Metal Levels in Electronic Cigarette Liquids Retailed in Romania

Abstract: The growing popularity of electronic cigarettes has raised several public health concerns, including the risks associated with heavy metals exposure via e-liquids and vapors. The purpose of this study was to determine, using atomic absorption spectrometry, the concentrations of Pb, Ni, Zn, and Co in some commercially available e-liquid samples from Romania immediately after purchase and after storage in clearomizers. Lead and zinc were found in all investigated samples before storage. The initial concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…The storage temperature could also affect the increase in metals in the fluid. In a recent study evaluating the metal concentrations of lead, nickel, and zinc in clearomizers, the concentrations of all three elements increased when the clearomizers were stored in a temperature range of 22–40° [ 40 ]. These increases in element/metal concentrations also varied with EC brand.…”
Section: Discussionmentioning
confidence: 99%
“…The storage temperature could also affect the increase in metals in the fluid. In a recent study evaluating the metal concentrations of lead, nickel, and zinc in clearomizers, the concentrations of all three elements increased when the clearomizers were stored in a temperature range of 22–40° [ 40 ]. These increases in element/metal concentrations also varied with EC brand.…”
Section: Discussionmentioning
confidence: 99%
“…The storage temperature could also affect the increase in metals in the fluid. In a recent study evaluating the metal concentrations of lead, nickel, and zinc in clearomizers, the concentrations of all three elements increased when the clearomizers were stored in 22-40° [40]. These increases in element/metal concentrations also varied with EC brand.…”
Section: Discussionmentioning
confidence: 93%
“…Table 1 summarizes the common additives and pollutants in vaping fluid, their mechanisms of pulmonary damage, or related toxicities. Increased use of E-cigarettes and ECs has raised numerous adverse health concerns involving the risks of heavy metals exposure via Els and vapors [145]. Current studies have confirmed that many heavy metals are present in both EC liquids and vapors at potentially harmful levels, which endangers both user and passive vaping [146].…”
Section: Cannabidiol (Cbd) Vaping Productsmentioning
confidence: 99%